Das russische philologische Seminar in Leipzig: das Seminar unter Ritschl und Lipsius (1873–1890) und der Versuch der Wiederbegründung (1911–1913) - Schröder, Wilt Aden (Hyperboreus, 2014)
Based on archival research, the paper traces the history of the Leipzig Philological Seminar (1873–1890) established sub auspiciis of Fr. Ritschl to provide professional training to the teachers of Classical languages from the Russian empire and East European Slavic countries. More than one hundred classicists graduated from the Leipzig Philological Seminar. There were outstanding scholars among them, including Th. Zielinski, E. von Stern, A. Sonny. An attempt was made to resume the Seminar in 1911–1913, however it failed due to the unfavourable political situation at the time.